A SYSTEMATIC LITERATURE REVIEW STUDY ON DA'WAH AND ISLAMIC ECONOMIC EMPOWERMENT - Hendra Cipta; Al Fakhri Zakirman (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Da'wah should encompass not just teachings on worship but also the promotion and education of the Islamic economy. These two fields should enhance and reinforce one another. This study aims to examine the influence of da'wah on the development of the Islamic economy, as well as the reciprocal impact of the Islamic economy on the dissemination of sharia values. A total of 513 papers, comprising 500 from Google Scholar and 13 from Scopus, underwent screening, eligibility evaluation, and quality rating in this study. The research methodology employed is qualitative, utilizing a systematic literature review approach following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) guidelines. The study's findings indicate that da'wah and economic empowerment are mutually reinforcing, contributing to Muslims' economic self-sufficiency and long-term viability. The propagation of da'wah by da'i, encompassing information on Islamic economics, can elevate societal literacy and catalyze advancing the empowerment of the Islamic economy. Similarly, the Islamic economy, encompassing halal tourism and Islamic financial products, functions as a means of da'wah to facilitate mua'malah transactions by Sharia principles.